The Influence of Online Customer Reviews and Brand Ambassadors on Consumer Purchase Interest Mediated by Attitude - Ricko Muhammad Farhan; Padmantyo, Sri (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the influence of online customer reviews and brand ambassadors on consumer purchase interest, with attitude examined as a mediating variable. Using a causal quantitative approach, data were gathered through structured questionnaires from 200 purposively selected respondents aged 18 and above who were familiar with Erigo's online reviews and brand ambassadors and had used the product. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that online reviews and brand ambassadors significantly affect consumer attitudes and purchase interest. While positive reviews enhance perceptions and credible ambassadors strengthen brand image, attitude was found to have no significant effect on purchase interest. It did not mediate the relationship between the independent variables and purchase interest. This finding suggests that other factors—such as price sensitivity, urgency of need, or situational influences—may play a stronger role in shaping consumer decisions than previously assumed by attitude-based models. Although this study offers relevant insights for digital marketing strategies, the use of purposive sampling and limited demographic scope restricts the generalizability of its findings and highlights the need for further research with more diverse populations and expanded theoretical frameworks.